The Future of Money - Cohen, Benjamin J. (Book collections on Project MUSE., 2004)
"Is globalization leading us toward a world of fewer and fewer currencies and, consequently, simplified money management? Many specialists believe this is the case, as the territorial monopolies national governments have long claimed over money appears to be eroding. In The Future of Money, Benjamin Cohen argues that this view - which he calls the "Contraction Contention"--Is wrong. Rigorously argued, written with extraordinary clarity, and thoroughly up-to-date, this book demonstrates that the global population of currencies is set to expand greatly, not contract, making monetary governance more difficult, not less."--Jacket.